2020
DOI: 10.1038/s41598-020-72440-6
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost dynamics and the risk of anthrax transmission: a modelling study

Abstract: A recent outbreak of anthrax disease, severely affecting reindeer herds in Siberia, has been reportedly associated to the presence of infected carcasses or spores released from the active layer over permafrost, which is thawing and thickening at increasing rates, thus underlying the re-emerging nature of this pathogen in the Arctic region because of warming temperatures. Anthrax is a global zoonotic and epizootic disease, with a high case-fatality ratio in infected animals. Its transmission is mediated by envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
(61 reference statements)
0
20
0
Order By: Relevance
“…This finding will increase the understanding of the regularity of the diseases and guide in epidemic prevention. Importantly, some infectious diseases, like HBV [47], HCV [48], HEV [49,50], Anthrax [51], Gonorrhea [52,53], Treponema pallidum [54], and Leptospirosis [55,56] are thought to be more sporadic rather than seasonal or cyclical. In our work, we found that they have distinct oscillatory properties despite relatively lower selectivity compared with other seasonal diseases.…”
Section: Plos Onementioning
confidence: 99%
“…This finding will increase the understanding of the regularity of the diseases and guide in epidemic prevention. Importantly, some infectious diseases, like HBV [47], HCV [48], HEV [49,50], Anthrax [51], Gonorrhea [52,53], Treponema pallidum [54], and Leptospirosis [55,56] are thought to be more sporadic rather than seasonal or cyclical. In our work, we found that they have distinct oscillatory properties despite relatively lower selectivity compared with other seasonal diseases.…”
Section: Plos Onementioning
confidence: 99%
“…Regional models with higher resolution can therefore be recommended for the monitoring and forecasts of weather conditions causing unfavorable epidemiological situations in cold climates. In addition, mathematical models can be applied on a local scale (Friedman and Yakubu 2013;Saad-Roy et al 2017;Gomez et al 2018;Stella et al 2020).…”
Section: Results In the Context Of Literature And Implications For Future Researchmentioning
confidence: 99%
“…Brucella spp., is a zoonotic bacteria that is one of the most widespread and economically impactful zoonosis affecting reindeer and can be transmitted to human via raw animal products, including from reindeer and caribou [ 138 , 139 ]. Anthrax, a global zoonotic and epizoonotic disease, is another bacterial pathogen identified in reindeer, particularly in relation to infected carcasses, as recently found in Siberian permafrost and therefore also indicative of a possible rise in the Arctic due to climate change [ 140 ]. Reindeer have in addition been found to carry Clostridium perfringens [ 141 ] and can suffer from severe bacterial intestinal infections and endotoxemia by Clostridium sp [ 142 , 143 ], while other bacteria inside the order Clostridiales aid in processing of lichen secondary metabolites [ 144 ].…”
Section: Discussionmentioning
confidence: 99%